KEWENANGAN GUBERNUR DALAM PENGELOLAAN DAN PEMANFAATAN PASIR LAUT DI DAERAH KHUSUS JAKARTA: Title Governor Authority in Marine Sand Management and Utilization in the Special Capital Region of Jakarta - Kalista Sofi Permana; Ninuk Wijiningsih (Reformasi Hukum Trisakti, 2026)
The use and management of marine sand are essential for development initiatives, environmental preservation, and the allocation of governmental power. In Jakarta, the rising need for marine sand for coastal reclamation and development projects presents particular legal issues, particularly regarding the Governor's power to regulate and monitor its usage. The Governor of the Special Capital Region of Jakarta's administration and usage of marine sand is the subject of this study, which seeks to determine if it complies with current legislation and guidelines. Using legislative and theoretical methodologies, the research makes use of a prescriptive legal research strategy. According to Law Number 23 of 2014 on Regional Government, Law Number 32 of 2014 on Marine Affairs, and Law Number 2 of 2024 on Jakarta, the Governor has the authority to oversee, regulate technical issues, and safeguard the coastal environment. However, the Governor's responsibilities have been limited to primarily coordination and monitoring since the passage of Law Number 11 of 2020 on Job Creation has shifted some licensing authority to the federal government. To ensure the sustainable use of marine sand in Jakarta in accordance with legal principles, there must be policy coordination between the central and regional authorities for its efficient management.